Study of morphometric indicators of structural units of lung tissue according to the forms of primary atelectasis (Texas Journal of Medical Science, 2026)
Qualitative indicators of primary atelectasis of the lungs, the degree and pathogenetic mechanism of macroscopic and microscopic changes in the lungs were studied. Qualitative indicators of primary atelectasis are assessed based on the color, size, degree of deviation from lung tissue, and lack of air filling of macroscopic and microscopic changes in the lungs. According to the pathomorphological signs of atelectasis development, 3 degrees are distinguished: 1) mild - alveolar thickening; 2) moderate - circulatory disorders due to pulmonary edema; 3) severe atelectasis - involvement of the lungs with secondary pathological tissue, i.e., pneumosclerosis, retention cysts of the bronchi, bronchiectasis. Depending on the prevalence and localization of the pathological process, atelectasis of the entire lung, lobar atelectasis, segmental atelectasis, and subsegmental atelectasis are distinguished. In the course of the study, morphometric indicators of structural units of lung tissue were studied in a total of 98 children, including 54 premature and 44 full-term newborns. Studies have shown that among maternal diseases, preeclampsia, eclampsia, infectious diseases, endocrine pathology and various extragenital diseases, as well as complications associated with the labor process, can be a risk factor for the development of primary atelectasis in the lungs of newborns to varying degrees. It was noted that primary atelectasis of the lungs in newborns occurs in most cases in premature infants, and the rate of development of diseases identified as a risk factor is also high.